Population and infestation status of Thaumatotibia leucotreta (Meyrick) in small-scale avocado growing in northern and southern zones of Tanzania - Juliana Godifrey Shikoshi; Mashamba Philipo; Patrick Alois Ndakidemi; Kelvin Mark Mtei; Angela Gerald Mkindi; Ernest Rashid Mbega (Cogent Food & Agriculture, 2025)
Thaumatotibia leucotreta is a challenging pest that significantly impact avocado fruit production in Tanzania. Larvae feeding reduces avocado fruit quality and yield, with up to 25% fruit losses reported in the northern region. However, current information on the pest’s population and infestation status in small-scale avocado-growing zones of Tanzania is limited. We investigated the effects of altitude, fruiting stage, and infestation by T. leucotreta during two avocado-producing seasons. Pheromones traps were placed in 40 avocado orchards to monitor T. leucotreta population weekly. Fruits were assessed for pest incidence based on observable larval symptoms on the fruit surface peculiar to T. leucotreta (frass presence). The results showed a significant (P ≤ 0.001) difference in T. leucotreta population in the midland areas of the two zones. The peak populations of moths were observed in February and August for the northern and southern zones, respectively, and the lowest in March and September, respectively. Significant (P ≤ 0.001) differences in moth abundance were recorded at different altitudes in each zone. Overall larval incidence on fruits indicated 49.3% infestation rate across zones. These findings would assist in designing and developing efficient control strategies and timely treatment applications to reduce pest incidence in Tanzanian avocado-growing areas.